Detection of Fetal Anomalies by Remotely Directed and Interpreted Ultrasound (Teleultrasound): A Randomized Noninferiority Trial - Whittington, Julie R.; Hughes, Dawn S.; Rabie, Nader Z.; Ounpraseuth, Songthip T.; Nembhard, Wendy N.; Chauhan, Suneet P.; Magann, Everett F. (American Journal of Perinatology, 2021)
Objective To determine the accuracy and reliability of remotely directed and interpreted ultrasound (teleultrasound) as compared with standard in-person ultrasound for the detection of fetal anomalies, and to determine participants' satisfaction with teleultrasound.Study Design This was a single-center, randomized (1:1) noninferiority study. Individuals referred to the maternal–fetal medicine (MFM) ultrasound clinic were randomized to standard in-person ultrasound and counseling or teleultrasound and telemedicine counseling. The primary outcome was major fetal anomaly detection rate (sensitivity). All ultrasounds were performed by registered diagnostic medical sonographers and interpretations were done by a group of five MFM physicians. After teleultrasound was completed, the teleultrasound patients filled out a satisfaction survey using a Likert scale. Newborn data were obtained from the newborn record and statewide birth defect databases.Results Of 300 individuals randomized in each group, 294 were analyzed in the remotely interpreted teleultrasound group and 291 were analyzed in the in-person ultrasound group. The sensitivity of sonographic detection of 28 anomalies was 82.14% in the control group and of 20 anomalies in the telemedicine group, it was 85.0%. The observed difference in sensitivity was 0.0286, much smaller than the proposed noninferiority limit of 0.05. Specificity, negative predictive value, positive predictive value, and accuracy were more than 94% for both groups. Patient satisfaction was more than 95% on all measures, and there were no significant differences in patient satisfaction based on maternal characteristics.Conclusion Teleultrasound is not inferior to standard in-person ultrasound for the detection of fetal anomalies. Teleultrasound was uniformly well received by patients, regardless of demographics. These key findings support the continued expansion of telemedicine services.Key Points
Keywords: telemedicine; teleultrasound; fetal anomalies; patient satisfaction